Host sensing and signal transduction during Toxoplasma stage conversion. Issue 5 (21st November 2020) - Augusto, Leonardo; Wek, Ronald C.; Sullivan, William J.
Abstract: The intracellular parasite Toxoplasma gondii infects nucleated cells in virtually all warm‐blooded vertebrates, including one‐third of the human population. While immunocompetent hosts do not typically show symptoms of acute infection, parasites are retained in latent tissue cysts that can be reactivated upon immune suppression, potentially damaging key organ systems. Toxoplasma has a multistage life cycle that is intimately linked to environmental stresses and host signals. As this protozoan pathogen is transmitted between multiple hosts and tissues, it evaluates these external signals to appropriately differentiate into distinct life cycle stages, such as the transition from its replicative stage (tachyzoite) to the latent stage (bradyzoite) that persists as tissue cysts. Additionally, in the gut of its definitive host, felines, Toxoplasma converts into gametocytes that produce infectious oocysts (sporozoites) that are expelled into the environment. In this review, we highlight recent advances that have illuminated the interfaces between Toxoplasma and host and how these interactions control parasite stage conversion. Mechanisms underlying these stage transitions are important targets for therapeutic intervention aimed at thwarting parasite transmission and pathogenesis. Abstract : Toxoplasma gondii is an intracellular parasite of animals that has infected one‐third of the human population. The parasite has a complex life cycle involving multiple hosts, exclusively using felids to complete the sexual stage, which culminates in the release of billions of dormant infectious oocysts into the environment. Within individual hosts, Toxoplasma can also convert into a latent tissue cyst that is transmitted through predation. The ability to shift between replicative and dormant stages is central to pathogenesis and transmission of Toxoplasma, necessitating an understanding of the molecular mechanisms driving stage conversion.